The Importance of Collaborative Project-Based Javanese Language Learning Model for Character Strengthening - Alfiah, Alfiah; Subyantoro, Subyantoro; Mardikantoro, Hari Bakti; Yuniawan, Tommi (Proceedings of International Conference on Science, Education, and Technology, 2025)
Javanese language learning has strategic potential in instilling noble character values that are in harmony with local wisdom and the vision of national education. However, the learning model that is still conventional is not yet fully able to answer the demands of strengthening students' character contextually. This study aims to describe the urgency of developing a collaborative project-based Javanese language learning model as an effective means of shaping students' character. The method used is qualitative descriptive research with data collection through literature studies and observation through questionnaires. The data subjects were Javanese language teachers of junior high schools, high schools and vocational schools in Central Java. The data analysis technique uses the Milles Huberman mobile interactive technique. The findings of the study show that collaborative project-based learning is not only able to increase students' active involvement in learning, but is also effective in fostering character values such as responsibility, cooperation, and social concern. The design of a Javanese language learning model that integrates the principle of collaboration in the context of real projects needs to be a priority for innovation based on local wisdom. The implications of the results of this study contribute to the development of a holistic and transformative instructional design in Javanese language learning. These findings also recommend the need to develop learning models that prioritize collaboration, active student participation, and the use of local contexts as learning resources to support character-based education transformation.